2004
DOI: 10.1103/physrevb.69.172407
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocrystalline anisotropy and orbital polarization in ferromagnetic transition metals

Abstract: The magnetocrystalline anisotropy energies ͑MAE's͒ of the ferromagnetic metals bcc Fe, fcc and hcp Co, and fcc Ni have been calculated by using the ab initio tight-binding method. Disentangling the strong correlation among the d orbitals with the Hamiltonian in the local spin-density approximation, we have investigated the orbital polarizations induced by the Hubbard U and Racah B. The experimental MAE of fcc Ni is found with the value of U close to that determined from experiments and used in other theories. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We would like to emphasize here that the model itself has a phenomenological character since it is not based on the spin-orbit coupling considerations. A more adequate approach should involve first principle calculations of the magnetic moments and MAE with atomic resolution, like in Co/Cu ( 5,33 ). However at the present state of the art this task remains difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to emphasize here that the model itself has a phenomenological character since it is not based on the spin-orbit coupling considerations. A more adequate approach should involve first principle calculations of the magnetic moments and MAE with atomic resolution, like in Co/Cu ( 5,33 ). However at the present state of the art this task remains difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum abinitio studies have revealed different anisotropy and magnetic moment at the surface of magnetic clusters embedded in matrices 5 . Synchrotron radiation studies have confirmed that both spin and orbital moments at the surface differ significantly from their bulk counterparts 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The one-particle dynamics of models for correlated lattice electrons can be determined, in principle, within the dynamical mean-field theory (DMFT) [9,10,11] which becomes exact in the limit of an infinite number of nearest neighbors (coordination number Z → ∞). The 'static approximation' to DMFT is the 'LDA+U' scheme which has been applied to a variety of correlated-electron systems [12,13,14]. Moreover, DMFT has been extended in various ways, e.g., a combination of the LDA-GW approximation and the DMFT has been put forward [15].…”
Section: Ferromagnetism: Whither Theory?mentioning
confidence: 99%
“…Recent correlated-electron theories remove the SDFT shortcomings only partially. For example, with LDA+U-type calculations it seems to be possible to adjust to experiment the orbital moment, the magnetic anisotropy, and the Fermi surface topology [13,14]; however, other quantities, especially the entire quasi-particle band structure, remain elusive within these correlated-electron theories.…”
Section: The Nickel Problemmentioning
confidence: 99%
“…The one-particle dynamics of models for itinerant ferromagnets can be determined, in principle, within the dynamical mean-field theory [31,32]. The 'static approximation' to DMFT is the 'LDA þ U' scheme which has been applied to itinerant ferromagnetism recently [33,34]. Moreover, DMFT has been extended in various ways, e.g.…”
Section: Whither Theory?mentioning
confidence: 99%